Pedagogical and research-practical achievements of the department of general surgery(to 100-th anniversary of the department of general surgery) - Trofimov, M. V.; Barannik, S. I.; Muntian, S. O.; Kryshen, V. P. (Medicni Perspektivi, 2018)
Pedagogical and research-practical achievements of the department of general surgery(to 100-th anniversary of the department of general surgery)